The influences of nutritional status and abdominal circumference systolic blood pressure in adult men - Ni'ma Hilyatin; Katrin Roosita; Rimbawan Rimbawan; Mohamad Rafi (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2024)
The prevention and management of hypertension through healthy lifestyle modifications is a challenge for public health. The prevalence of hypertension among Indonesians was 34,1%. Lifestyle behaviors such as body mass index, central obesity, and sodium intake are associated with the risk of hypertension. This study aimed to analyze the influence of nutritional status and abdominal circumference on blood pressure in adult men. This cross-sectional research was conducted in Sukajadi Village, Bogor, between 2022-2023. The subjects were 73 purposively selected adult men. Data on subject characteristics were obtained through interviews. Anthropometric data were obtained by measuring abdominal circumference, body weight, and body height to assess the body mass index (BMI). Consumption data were collected using SQ-FFQ. The data analysis was performed using a linear regression test with a significance level of 95%. The results showed that Body mass index (p=0,007) and abdominal circumference (p=0,005) affected systolic blood pressure, while sodium intake (p=0,906) was not related to systolic blood pressure in adult men. Conclusions: Body mass index and abdominal circumference greatly influenced the systolic blood pressure. Further studies are needed to determine the various factors that influence systolic blood pressure and the risk of hypertension.